Adaptive Genetic Divergence Despite Significant Isolation-by-Distance in Populations of Taiwan Cow-Tail Fir (Keteleeria davidiana var. formosana) - Shih, Kai-Ming; Chang, Chung-Te; Chung, Jeng-Der; Chiang, Yu-Chung; Hwang, Shih-Ying (Frontiers in Plant Science, 2018)
Double digest restriction site-associated DNA sequencing (ddRADseq) is a tool for delivering genome-wide single nucleotide polymorphism (SNP) markers for non-model organisms useful in resolving fine-scale population structure and detecting signatures of selection. This study performs population genetic analysis, based on ddRADseq data, of a coniferous species, Keteleeria davidiana var. formosana, disjunctly distributed in northern and southern Taiwan, for investigation of population adaptive divergence in response to environmental heterogeneity. A total of 13,914 SNPs were detected and used to assess genetic diversity, FST outlier detection, population genetic structure, and individual assignments of five populations (62 individuals) of K. davidiana var. formosana. Principal component analysis (PCA), individual assignments, and the neighbor-joining tree were successful in differentiating individuals between northern and southern populations of K. davidiana var. formosana, but apparent gene flow between the southern DW30 population and northern populations was also revealed. Fifteen of 23 highly differentiated SNPs identified were found to be strongly associated with environmental variables, suggesting isolation-by-environment (IBE). However, multiple matrix regression with randomization analysis revealed strong IBE as well as significant isolation-by-distance. Environmental impacts on divergence were found between populations of the North and South regions and also between the two southern neighboring populations. BLASTN annotation of the sequences flanking outlier SNPs gave significant hits for three of 23 markers that might have biological relevance to mitochondrial homeostasis involved in the survival of locally adapted lineages. Species delimitation between K. davidiana var. formosana and its ancestor, K. davidiana, was also examined (72 individuals). This study has produced highly informative population genomic data for the understanding of population attributes, such as diversity, connectivity, and adaptive divergence associated with large- and small-scale environmental heterogeneity in K. davidiana var. formosana.